Impact of Virtual Reality on pre-university students - Petru-Iulian GRIGORE; Corneliu Octavian TURCU (Revista Română de Informatică și Automatică)
Integrating Virtual Reality (VR) into educational environments represents a significant advancement in teaching and learning. Traditional text-based instruction can diminish student engagement, while VR can fully immerse students, enhancing motivation, understanding, and participation. This study explores the impact of VR in education, highlighting its ability to engage students and improve information retention. However, challenges such as accessibility, cost-effectiveness, and safety need to be addressed. Student feedback highlighted VR's engaging and immersive nature but noted technical issues and a need for more diverse content. Recommendations for improvement include expanding content diversity, enhancing visual and audio quality, reducing equipment costs, and providing additional support for students with limited technology skills. Ultimately, VR shows great promise in transforming education by creating interactive and immersive learning experiences, with ongoing research and development being essential to fully realize its potential.